Measures to Prevent the Violation of the Rights of Content Creators in Digital Environment: Case Study of Nigeria - A. D. Aina-Pelemo; I. Bassey; G. O. Akpojaro (Journal of Digital Technologies and Law, 2024)
Objective: to determine the level of protection of the rights of content creators in social media and to develop measures to prevent offenses in this area.Methods: to achieve the objective, the sociological and legal cognitive tools were used, including the doctrinal method of researching the subject area, obtaining “first-hand” data and taking into account the factors and circumstances of influence. The main results were obtained through the sociological method used to collect data based on a specially developed questionnaire with four research questions: (1) what are the perceptions and opinions of third parties or users regarding the role of a content creator? (2) are the rights of content creators regarding their works violated? (3) what are the ways to protect the created content from infringement by platforms? and (4) how can the rights of content creators be protected? The empirical findings and generalizations were based on a combination of analyses, including content analysis of primary and secondary legal sources.Results: In recent years, the content generation in social media has evolved into a complex industry that is transforming both the traditional understanding of creative expression and the implementation of intellectual property rights. Using the Nigerian experience as a case study, the authors examine the rights and protection measures provided to digital content creators under intellectual property law. The study shows that there is currently not enough scholarly work in this area or developed legislation to protect the social media content. It is concluded that there is a need for improved legislation on the protection of rights in the sphere of social media content. In the absence of such legislation, creators of online works should resort to more radical methods in enforcing their rights in order to reduce intellectual property misappropriation. Creators of such works are suggested to ensure the protection of their rights based on the fair use doctrine principles.Scientific novelty: the study is structured around research questions concerning infringements and remedies for content creators. The questions were addressed to respondents from different countries, a large proportion of whom specialize mainly in content creation in various social spheres through several media platforms and social networks.Practical significance: the article conclusions and recommendations may minimize the risks of infringement of intellectual property rights of content creators, which may arise with the widespread use of social networks, as well as increase the level of protection of rights to works created in the form of online content.